Compostos orgânicos voláteis (VOCs): caracterização e alternativas de remediação - Martins, Gabriel de Freitas (Universidade Federal de São Carlos, 2022)
Volatile organic compounds (VOCs) are present in human daily life, which can be emitted biogenically or anthropically. These are compounds that under environmental conditions have high volatility, they have a boiling point of 50 - 100°C up to 250 - 260°C, some have carcinogenic potential, and most of them react with nitrogen oxides, producing carcinogenic compounds. Contamination/pollution of aquatic environments by VOCs occurs through industrial, domestic and even plantation waste. For the analysis of VOCs, the sample preparation step is very important, as it is necessary to have pre-concentration and sometimes isolation. There are several sample preparation techniques for VOC analysis, including solvent extraction, solid phase extraction, and HeadSpace transfer. Subsequently, the analyzes are usually performed by chromatography. The most widespread method of removing VOCs from the aquatic environment is the volatilization of them, which depends on several properties of each VOC. The most widely used technique is activated carbon removal, but for halogenated VOCs another technique is required, such as biodegradation. It is concluded that previously developed techniques for extraction, analysis and remediation of VOCs found in water are efficient, however, it is still necessary to study new methods of extraction, analysis and removal.
Volatile organic compounds (VOCs): characterization and remediation
Keywords: VOCs; Água; Análise; Extração; Remoção; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ANALISE DE TRACOS E QUIMICA AMBIENTAL